2020
DOI: 10.3151/jact.18.588
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Water Redistribution from Large Pores to Fine Pores after Water Uptake in Hardened Cement Paste

Abstract: During sorption, the microstructural evolutions of two different cement pastes (with water-to-cement ratios of 0.40 and 0.55) are studied via proton-nuclear-magnetic-resonance relaxometry. The water uptake test is performed for samples dried at 105°C under three different temperatures of 20°C, 40°C, and 60°C for the first twenty-six days of sorption. It is observed that the water went first to the larger pores before migrating to the finest ones. This behavior is accelerated with increasing temperature. The ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In a companion paper, Kiran et al (2020) showed that the water exchange from large pores to fine pores in different temperature conditions could be monitored by 1 H-NMR relaxometry. These results could be attributed to dynamic microstructural changes in C-S-H during water absorption.…”
Section: Opc-ls-mentioning
confidence: 99%
See 2 more Smart Citations
“…In a companion paper, Kiran et al (2020) showed that the water exchange from large pores to fine pores in different temperature conditions could be monitored by 1 H-NMR relaxometry. These results could be attributed to dynamic microstructural changes in C-S-H during water absorption.…”
Section: Opc-ls-mentioning
confidence: 99%
“…In a previous study (Kiran et al 2020), the local water exchange between larger pores and fine pores was modeled by Eq.…”
Section: Local Moisture Water Exchange From Larger Pores To Fine Poresmentioning
confidence: 99%
See 1 more Smart Citation
“…The scarcity of such data for nuclear structures has been reported in the literature [35]. The redistribution of water from large to fine pores in hardened concrete [36] is another aspect which would be dependent on microstructure of the concrete and thus could be typical for Indian concrete. Transient creep strains in concrete when exposed to fire, particularly for member temperatures above 500°C, have been reported in the literature [37], and these factors would influence the response of concrete structures to fire.…”
Section: Generation Of Fire/elevated Temperature Test Data For Indianmentioning
confidence: 99%
“…Ordinary Portland cement, OPC, is commonly used for cementation (Glasser and Atkins 1994) since the calcium silicate hydrate or C-S-H gel, the main hydration product of OPC, has a large surface area with many sorption and reaction sites in which the contaminants can be retained (Real et al 2002;Volchek et al 2011). Moreover, the C-S-H gel has low diffusibility and solubility due to its microstructure, which reduces the mobility of the contaminants and prevents their release (Hewlett 2003;Kiran et al 2020).…”
Section: Introductionmentioning
confidence: 99%